Pengaruh Masuknya Penambahan Pembangkit Baru Kedalam Jaringan 150 kV Pada Kapasitas Circuit Breaker - Emelia, Emelia; Sukma, Dian Yayan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This study aimed to obtain the appropriate capacity circuit breaker on the electric power system of Riau using bus impedance matrix method in determining the flow of short circuit in the electric power system of Riau. This research was conducted in two conditions, namely the current state (exsisting) and the conditions at the time of entry of a new generation into the electricity system interconnection network Riau region in this regard Tenayan power plant with a capacity of 2x110 MW.The results showed that the capacity of the circuit breaker that is currently installed on the electrical system Riau region is still larger than the three-phase short-circuit current simteris that may occur at this time of 12,375kA and at the time of entry of a new generation of 13,215kA so it can be said that the electrical system Riau region still able to withstand short circuit currents that may occur at the time of entry of the power supply from new power plants that have been planned.Keyswords: capacity circuit breaker, circuit breaker, short circuit